Energy Efficient Homes: Indoor Air Quality and Energy - Hyun-Jeong Lee; Kathleen C. Ruppert; Wendell A. Porter (EDIS)
FCS-3275, a 3-page fact sheet by Hyun-Jeong Lee, Kathleen C. Ruppert, and Wendell A. Porter, explains factors that affect indoor air quality and ventilation strategies to maintain good indoor air quality in an energy efficient home. Includes references. One of an Energy Efficient Homes series. Published by the UF Department of Family Youth and Community Sciences, June 2008.